Faktor Internal dan Faktor Eksternal yang Mempengaruhi Terjadinya Demokratisasi di Myanmar - Mirajiah, Risalatu (Jurnal Ilmiah HUBUNGAN INTERNASIONAL, 2013)
Abstract: Democratization in Myanmar has drawn international attention, when on April 1, 2012military junta held a free, fair general election. The success of Myanmar in holding the general electionwould become a new era of changes that was occurring domestically. Positive responses on thechanges were shown by not only Myanmars people but also the whole international comunities whichhad previously pressured the state due to various violations of human right and democracy. Basically,some democratizing efforts had begun since the government drafted a new constitution in 2008, up tothe winning of Thein Sein as President in the 2010 preliminary elections. Under Thein Sein leadership,there have been much changes leading to democracy, such as the achievement of ceasefire, economicimprovement, the release of political detainees, mass media freedom, general elections, and thereestablishment of parliamentary functions. The question in this paper was, âHow these internal andexternal factors influence the occurrence of democratization in Myanmar?â In this paper, the writerdrew on the theories of democratization in describing the internal and external factors that haveinfluence on the occurrence of democratization, by the three approaches, namely, modernization,transition, and structural approaches, from David Potter. The paper results indicated that the aim of themilitary junta at implementing the democratization was due to some internal factors in a domesticscope, predominated by domestic actors, and some external factors in a framework of democratizationwaves by a reason of spreading or promoting democratic values, as well pressures and other sanctions.The entire threats have led to the decline of military junta legitimacy in political arena, and expulsionby international world. Therefore, the writer concluded that the relationship between the internalfactors and external factors would determine the continuity of democratization in Myanmar.Keywords : Democratization, Internal Factors, External Factors, Military Junta, Myanmar